Doping of polyaniline and derivatives induced by X-ray radiation - Malmonge, J. A. [UNESP]; Mattoso, L. H. C. (Elsevier, 1997)
Thin films of chemically synthesized polyaniline and poly(o-methoxyaniline) were exposed to ionizing X-ray radiation and characterized by radiation induced conductivity measurements, ultraviolet-visible spectroscopy, electron paramagnetic resonance, electrical conductivity and solubility measurements. Samples irradiated in vacuum or dry Oxygen atmosphere did not have their electronic spectra changed. However, under humid atmosphere the energy of the excitonic transition was decreased and accompanied by a great conductivity increase. The results indicate that doping of polyaniline can be induced by X-ray radiation which might be of great interest for applications on lithography and microelectronics.
Keywords: Polyaniline and derivatives; Radiation induced conductivity; UV-Vis absorption; X-ray radiation; Amines; Derivatives; Doping (additives); Electric conductivity measurement; Light absorption; Paramagnetic resonance; Radiation effects; Solubility; Synthesis (chemical); Ultraviolet spectroscopy; X rays; Polyanilines; Plastic films